Courts Caught in Conflict? Institutional Trust and Social Conflict. - DOI 10.5935/2448-0517.20190018 - Cox, Joseph M. (Juris Poiesis - Qualis A3, 2019)
According to positivity theory, the public's exposure to the American judicial system and the judiciary's unique set of symbols and processes tends to lead individuals to confer on the institution legitimacy and trust through mechanisms often not available to other political actors. This paper focuses on whether this theory operates outside of the American context, arguing that the legitimacy conferred by domestic audiences upon domestic judiciaries will be less variable than the legitimacy reposed in other governing actors. However, moving to a comparative context implicates a number of potentially additional factors, including the influence of variation across regime-types, legal systems, and issue areas. Are courts inherently unique, as suggested by positivity theory, or does the resiliency of courts vary across different institutional contexts? In order to answer this question, this study leverages survey data from the Latinobarómetro and the Afrobarometer to measure levels of public trust in several governing institutions, including, but not limited to, the judiciary, the executive, and the legislature, to analyze whether institutional legitimacy varies across different governmental actors in the presence of public opposition to government policy or across different legal institutional contexts. Public discontent with policy is measured using data coded by the Social Conflict Analysis Database, which identifies instances of demonstrations, riots, and strikes. As a measure of the institutional context within which a judiciary operates, the analyses leverage a latent variable of judicial independence created by Linzer and Staton (2015). The paper's statistical analyses provide evidence to support the distinctiveness of judiciaries, finding that social conflict can impact negatively public trust in executives and legislative institutions, yet exert no influence on public trust in judiciaries. Furthermore, the empirical results indicate that high levels of judicial independence can be converted to higher levels of trust in the judiciary.